Mental health challenges of recent immigrants in precarious work environments — a qualitative study - Shankar, Janki; Chen, Shu-Ping; Lai, Daniel W. L.; Joseph, Shawn; Narayanan, Rhea; Suleman, Zabin; Ali, H M Ashraf; Kharat, Priyadarshini (Frontiers in Psychiatry, 2024)
Introduction Recent immigrants from racialized minority backgrounds and those who are not proficient in the local language are some of the most vulnerable members of society. Despite having postsecondary educational qualifications and permanent residency status, many are engaged in precarious employment. There is a scarcity of research that has explicitly focused on the work experiences and mental health challenges faced by these immigrants. Methods Using a grounded theory approach and semi-structured face-to-face interviews, this study examined the work experiences and mental health challenges of 42 recent immigrant employees from two cities in Canada who were working in various industries and engaged in precarious employment. Findings Eighty-one percent of the employee participants were overqualified for their jobs. Findings highlighted several ongoing mental problems that participants experienced, stemming from challenging physical and psychological workplace conditions, negative mindsets associated with their recent immigrant status, and other contextual factors and barriers. However, various coping strategies, both constructive and unconstructive, were used to address this mental distress. Discussion The study proposes a multidimensional approach to address workplace conditions to promote good mental health for these employees. This includes preventative programs for raising awareness among employers about the importance of recent immigrant employees’ mental health and well-being and policy and legislation changes to ensure the employer’s commitment to creating a safe and culturally friendly workplace. The approach also recommends that recent immigrant employees receive occupational health and safety training, learn about Canadian workplace norms and culture, and have access to professional healthcare services.